Influence of intraocular astigmatism on the correction of myopic astigmatism by femtosecond laser small‐incision lenticule extraction. Issue 5 (May 2015) - Qian, Yishan; Huang, Jia; Chu, Renyuan; Zhao, Jing; Li, Meiyan; Zhou, Xingtao; Olszewski, Emily; Wang, Yutung
Abstract : Purpose : To evaluate the influence of the origin of astigmatism on the correction of myopia or myopic astigmatism by femtosecond laser small‐incision lenticule extraction (SMILE). Setting : Ophthalmology Department, Eye and ENT Hospital, Shanghai, China. Design : Prospective case series. Methods : Small‐incision lenticule extraction was performed to correct myopia or myopic astigmatism. Ocular residual astigmatism (ORA) was determined by vector analysis using manifest refraction and Scheimpflug camera imaging of the anterior cornea. Patients were divided into 2 groups according to ORA (high >1.0 diopter [D]; low ≤1.0 D), and procedural efficacy was compared. Patients were examined preoperatively and 1, 3, and 6 months postoperatively. Results : This study comprised 122 right eyes of 122 patients. No significant difference was found in the preoperative manifest astigmatism (target‐induced astigmatism [TIA]) between the low ORA group (n = 67) and high ORA group (n = 55). The mean postoperative manifest astigmatism was higher in the high ORA group at all postoperative timepoints (1 month: t = 2.182, P =.031; 3 months: t = 2.30, P =.023; 6 months: t = 2.193, P =.03). The mean index of success (postoperative astigmatism/TIA) was 0.68 in the high ORA group and 0.34 in the low ORA group 1 month postoperatively ( t = 2.531, P =.013); 0.73 and 0.39, respectively, at 3 months ( t = 2.689, P =.008); and 0.77 and 0.46, respectively, at 6 months ( t = 2.105, P =.037). Conclusion : Small‐incision lenticule extraction was effective in correcting astigmatism but may be less effective in correcting ORA. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.